Validation of the Greek version of Euthanasia Attitude Scale in the general population: A Quantitative Study - Provias, Georgios; Argyrou, Ourania; Theofanidis, Dimitrios (Health & Research Journal, 2025)
In examining the broader ethical implications of euthanasia, which is defined as the ace of ending one’s life with the intention of alleviating suffering, it is essential to consider ethical principles such as autonomy and the right to die. Euthanasia is a complex and ethically sensitive issue that continues to spark heated debate globally. Understanding public opinions toward euthanasia is critical for informing policy and healthcare decision-making. This study attempted to validate the Euthanasia Attitude Scale in the Greek general population since this issue affects both healthcare workers and the public. A cross-sectional study design was adopted with a sample of 120 Greek adults who completed a questionnaire which included demographic data and the Euthanasia Attitude Scale. The Cronbach's alpha was determined at a=0.950 for all questions, indicating that the questionnaire has a high internal consistency. The Kaiser–Meyer–Olkin (KMO) measure of sampling adequacy indicated that factor analysis was appropriate for the data (KMO = 0.913), while Bartlett’s test of sphericity was statistically significant (p < 0.001), confirming the suitability of the correlation matrix for factor extraction. The components had statistically significant positive relationships with the overall Euthanasia Attitude Scale (p<0.001). The assessment of the validity and reliability of the Euthanasia Attitude Scale demonstrated that it is a psychometrically sound instrument for evaluating the general population’s attitudes and perceptions toward euthanasia, and can be effectively used to measure individuals’ proclivity toward its acceptance. The scale may serve as a valuable tool for informing public health policies by offering insight into societal attitudes, thereby guiding ethical decision-making related to euthanasia legislation and healthcare practice.